84.8k views
4 votes
What is the positive solution to the equation 0 = –x2 + 2x + 1? Quadratic formula: x = StartFraction negative b plus or minus StartRoot b squared minus 4 a c EndRoot Over 2 a EndFraction –2 + StartRoot 2 EndRoot 2 – StartRoot 2 EndRoot 1 + StartRoot 2 EndRoot –1 + StartRoot 2 EndRoot

User Ketsy
by
4.4k points

2 Answers

3 votes

Answer:

The answer is C

Explanation:

User Kumarharsh
by
5.1k points
5 votes

Answer:

See attached for a "Neat" quadratic formula.

a = -1

b = 2

c = 1

x = [-2 +- sqr root( 4 -4*-1*1)] / -2

x = [-2 +- sqr root( 4 -4*-1*1)] / -2

x = [-2 +- sqr root(8)] / -2

x1 = (-2 +2.8284271247) / -2

x1 = .8284271247 / -2

x1 = -0.41421

x2 = (-2 -2.8284271247) / -2

x2 = ( -4.8284271247) / -2

x2 = 2.4142135624

So the equation has the positive solution of

2.4142135624

Explanation:

What is the positive solution to the equation 0 = –x2 + 2x + 1? Quadratic formula-example-1
User Vivek Kodira
by
5.1k points